In-vitro antioxidant and cytotoxic activities of ethyl acetate extract of Holigarna ferruginea - Manjunath, Kumbar Mudakappa; Krishnamurthy, Yelugere Linganaik (Current Botany, 2023)
Higher plants have long been used as traditional medicines to treat human ailments. Approximately 80% of people worldwide utilize plants as safe sources of medicines to heal human diseases via a totally new medicinal system. Holigarna ferruginea is an indigenous medicinal tree plant in the Anacardiaceae family. The plant has a wide range of physiologically active chemicals. GC-MS was used to screen phytochemical substances, while FTIR was used to identify functional groups. GC-MS study revealed 10 major bioactive phytochemical substances that belong to functional groups such as secondary amines, alcohols, ethers, esters, carboxylic acids, and anhydrides. These diverse active phytochemicals have been discovered to have a wide range of actions that may aid in the prevention of illnesses. Higher quantities of phytochemical substances were found in ethyl acetate extracts of leaves. As a result, the extract possesses anticancer and antioxidant activities against Humans Breast cell lines (MCF-7). The viability was reduced when the concentrations of the ethyl acetate extract of H. ferruginea leaves were increased and it may help in the discovery of an ideal therapeutic agent in novel drugs as well as nutritional supplements.